Result of Law on Construction of Flats which are Granted Ownership Rights Over the Building Use Rights - Khoeron Khoeron (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The study, entitled